Modern Tools for Genetic Engineering - Kormann, Michael S.D (IntechOpen, 2016)
Site-specific endonucleases create double-strand breaks within the genome and can be targeted to literally any genetic mutation. Together with a repair template, a correction of the defective locus becomes possible. This book offers insight into the modern tools of genome editing, their hurdles and their huge potential. A new era of in vivo genetic engineering has begun.